2021
DOI: 10.1039/d1sc04023e
|View full text |Cite
|
Sign up to set email alerts
|

Single-ion conducting polymer electrolytes as a key jigsaw piece for next-generation battery applications

Abstract: As lithium-ion batteries have been the state-of-the-art electrochemical energy storage technology, overwhelming demands for energy storage on a larger scale have triggered the development of next-generation battery technologies possessing high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 167 publications
(185 reference statements)
0
60
0
Order By: Relevance
“…[19][20][21] Nevertheless, the addition of plasticizers and crosslinking polymers in PCE membranes reduces the mechanical strength, thermal stability, and electrochemical performance. 22 Thus, successful implementation of PCE in real solid-state batteries is yet to be realized. In order to obtain an improved PCE membrane with higher conductivity, ionic conductors may be mixed into polymer matrix CE as a ller to enhance the mechanical, thermal, and electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Nevertheless, the addition of plasticizers and crosslinking polymers in PCE membranes reduces the mechanical strength, thermal stability, and electrochemical performance. 22 Thus, successful implementation of PCE in real solid-state batteries is yet to be realized. In order to obtain an improved PCE membrane with higher conductivity, ionic conductors may be mixed into polymer matrix CE as a ller to enhance the mechanical, thermal, and electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , 12 , 13 , 14 , 15 ] Recently, studies on the mathematical modeling of ASSBs have been reported. [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] However, describing the cell potential by Poisson's equation instead of directly modeling charge transport is not conducive to 3D modeling. [ 16 ] SSEs can be divided into binary‐ion conductors and single‐ion conductors based on whether both lithium cations and anions can move or not.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] SSEs can be divided into binary‐ion conductors and single‐ion conductors based on whether both lithium cations and anions can move or not. [ 17 ] The battery with a single‐ion conducting electrolyte has an advantage over that with a traditional binary electrolyte, especially at high discharge rates, due to the large concentration polarization in the latter. [ 18 ] When modeling lithium‐ion transport in a single‐ion conducting electrolyte, a uniform distribution of lithium‐ion is usually assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Even after considerable efforts of the scientific community, Gao, et al have recently published a review discussing the perspectives on current challenges and future directions of SPEs. 37 In their conclusions, the ionic conductivity at room temperature and below is still unsatisfactory for their practical applications.…”
Section: Introductionmentioning
confidence: 99%